2015
DOI: 10.1007/s10916-015-0311-6
|View full text |Cite
|
Sign up to set email alerts
|

A Type-2 Fuzzy Image Processing Expert System for Diagnosing Brain Tumors

Abstract: The focus of this paper is diagnosing and differentiating Astrocytomas in MRI scans by developing an interval Type-2 fuzzy automated tumor detection system. This system consists of three modules: working memory, knowledge base, and inference engine. An image processing method with three steps of preprocessing, segmentation and feature extraction, and approximate reasoning is used in inference engine module to enhance the quality of MRI scans, segment them into desired regions, extract the required features, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…First, by [19,21,28], such that [19] and [21] both are direct applications to a humanoid robot vision system, although both focused the use of IT2 FLS in different ways, as the first was used for object sample selection and the later was used for feature validity; and [28] is an application in auroral image segmentation. Secondly, the rest of the papers focused their algorithms to specifically solve medical imaging databases of different natures [18,20,22,27,29,31,33], using image segmentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, by [19,21,28], such that [19] and [21] both are direct applications to a humanoid robot vision system, although both focused the use of IT2 FLS in different ways, as the first was used for object sample selection and the later was used for feature validity; and [28] is an application in auroral image segmentation. Secondly, the rest of the papers focused their algorithms to specifically solve medical imaging databases of different natures [18,20,22,27,29,31,33], using image segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that, although most research papers used variations of the IT2 FCM clustering algorithm, some papers solely used IT2 FLSs as some type of expert system [20,23,27,28,31]. Some even used hybrid versions of IT2 FLS or IT2 FCM, such as Interval-Valued Possibilistic Fuzzy C-Means (IVPFCM) [7] and Extended Type-2 Fuzzy Information Theory (ET2FIT) [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the high uncertainty of some clinical symptoms required more accuracy to get acceptable results. Zarinbal et al [19,20] developed a type-2 fuzzy image processing expert system to diagnose brain tumors. They evaluated the system performance using 95 MRI scans, showing good capacity of diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…They mimic the decision-making abilities of a human expert, and they are designed to solve complex problems by reasoning. Expert system applications include, among others, medicine [29,53,60], diagnosis and control of power systems [26,27], evaluation of journal grades [61], information systems investment evaluation [19], transport management [31,51], industry [14,38] and sport [12,15,32,33,39].…”
Section: Introductionmentioning
confidence: 99%